2021
DOI: 10.5194/bg-18-1917-2021
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of fertilization on grassland productivity and water quality across the European Alps under current and warming climate: insights from a mechanistic model

Abstract: Abstract. Alpine grasslands sustain local economy by providing fodder for livestock. Intensive fertilization is common to enhance their yields, thus creating negative externalities on water quality that are difficult to evaluate without reliable estimates of nutrient fluxes. We apply a mechanistic ecosystem model, seamlessly integrating land-surface energy balance, soil hydrology, vegetation dynamics, and soil biogeochemistry, aiming at assessing the grassland response to fertilization. We simulate the major w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 113 publications
1
15
0
Order By: Relevance
“…Dry matter biomass increases as fertilizer doses increase. Significant biomass increases were also obtained by other researchers in this field [ 51 , 52 , 53 , 54 , 55 , 56 ]. Following this study, the use of fertilizers in moderate doses, namely the application of a 10 t/ha −1 manure or N 50 P 25 K 25 , will provide an increase in biomass and exert a minor influence on the diversity of grasslands, being close to the traditional use of grasslands in the Transylvanian Plain (our study area).…”
Section: Discussionsupporting
confidence: 70%
“…Dry matter biomass increases as fertilizer doses increase. Significant biomass increases were also obtained by other researchers in this field [ 51 , 52 , 53 , 54 , 55 , 56 ]. Following this study, the use of fertilizers in moderate doses, namely the application of a 10 t/ha −1 manure or N 50 P 25 K 25 , will provide an increase in biomass and exert a minor influence on the diversity of grasslands, being close to the traditional use of grasslands in the Transylvanian Plain (our study area).…”
Section: Discussionsupporting
confidence: 70%
“…The model can be used for distributed simulations at catchment scales or applied as one‐dimensional vertical model as was implemented in this study. A detailed description of T&C’s structure and process parameterizations is presented in Fatichi et al (2012) and it has been shown to have significant predictive capability across a range of ecosystems worldwide (e.g., Botter et al, 2021; Fatichi & Ivanov, 2014; Fatichi et al, 2012, 2014; Mastrotheodoros et al, 2017, 2020; Manoli et al, 2018; Paschalis et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…The physically based model Tethys-Chloris (T&C) is used to simulate the mass, energy, and water fluxes at the point scale at the five Peruvian study sites. T&C is a land surface model with an hourly time step that can resolve the surface energy balance, soil and vegetation dynamics, processes of runoff generation and flow routing, and the evolution of snow and ice packs (see Botter et al, 2021;Fatichi et al, 2012aFatichi et al, , 2012bFatichi &Pappas, 2017 andMastrotheodoros et al, 2020 for a description of the distributed model and its applications). For this study, we use it at the point scale for computation of the surface energy fluxes and snow and ice mass balance.…”
Section: Tethys-chloris Energy and Mass Balance Modelmentioning
confidence: 99%